School climate and its relationship to the professional performance of male and female teachers in Dhi Qar Governorate (Damu Journal of Sport Sciences, 2024)
The importance of the research crystallized in identifying the nature of the school climate and its relationship to the professional performance of male and female teachers of education in Dhi Qar Governorate and knowing the role of this climate in their professional performance and identifying the most important obstacles that prevent the availability of an appropriate school climate. The research problem focused on the fact that the importance of educational work and what this role requires in terms of distinguished professional performance can only be acquired by providing the appropriate school climate, which was not available in the appropriate form in our schools. Hence, the researcher saw the need to conduct this study with the aim of highlighting the role of the school climate and its relationship to the professional performance of male and female teachers of education in Dhi Qar Governorate. The aim of the research is to:- Build and validate a scale of school climate for male and female teachers of education in Dhi Qar Governorate.- Building and standardizing the professional performance scale for male and female education teachers in Dhi Qar Governorate.- Identifying the type of relationship between school climate and professional performance of male and female education teachers.The researcher used the descriptive approach using the survey method and correlational and comparative studies, due to its suitability and the nature of the current study.The researcher used the Statistical Package for Social Sciences (SPSS)The researcher came out with several conclusions, the most important of which were:1- The emergence of a high and very high level with low frequencies and percentages in the scale of professional performance of teachers.2-The high percentages and frequencies at a weak and very weak level are mainly caused by the lack of a suitable school climate for the work of education teachers.3-The school climate differs from one school to another, because each school has its own climate